Developing critical thinking skills in the argumentative writing of tertiary level students in a blended learning environment - Shahsavar, Zahra (2012)
Argumentative writing has been recognized as an essential skill expected of tertiary level students. However, many students do not display critical thinking in their language skills such as argumentative writing, and most instructors have yet to fully consider the major role of critical thinking in students’ writing. This study aimed to develop critical thinking skills in the argumentative writing of tertiary level students in a blended learning environment. The study employs a mixed-method research design to integrate quantitative and qualitative data collection and analysi . Participants were an intact class of tertiary level students enrolled in an obligatory course. In the quantitative data collection and analysis, a quasi-experiment was conducted to investigate the effects of critical thinking skill training and field-dependency on the students’ extent of critical thinking shown in argumentative writing on the blog and their perception of the course blog before and after the training. The Group Embedded Figure Test was used to identify and categorize the students into field-dependent or field-independent. The Cornell Critical Thinking Test Level X and the Course Blog Perception Questionnaire were used to assess students’ critical thinking ability and perception of the course blog respectively. Results showed that field dependency did not have a significant effect on students’ criticalness on their blogging; however, field independent students seemed to take more thought in asking critical questions. Moreover, the critical thinking skill training had a significant positive effect on students’ perception of the course blog. Besides, both field dependent and field independent students perceived that using the course blog was effective in improving their writing skill. In the qualitative data collection and analysis, a text analysis approach was employed. Students’ blog posts and comments were collected and analyzed by applying two critical thinking assessment models: Newman, Webb, and Cochrane’s (1996) critical thinking model, and Paul and Elder’s (2007) Universal Intellectual Standard model. The results revealed that the critical thinking skill training did cause the significant increase in students’ critical thinking ability in their blogging that might have led to their improved argumentative writing skill. The triangulation of the quantitative and qualitative analyses further supported the conclusion that critical thinking skills can be trained and the training can make a significant improvement on students’ critical thinking ability. The study suggests a new method of training critical thinking skills in a blended learning environment to improve students’ argumentative writing. Critical thinking training applied in this study can be considered effective and educators may adopt it to promote critical thinking among students. If students learn the skill and language of critical thinking, they can apply it not only in their argumentative writing, but also into every subject they take and every discussion they engage in.